Jakob Böhmes syn på den religiøse erfaring: et religionspsykologisk perspektiv - Bojesen, Lars Bo (Dansk teologisk tidsskrift, 2008)
Resumé The present article excavates a central question in the thought of Jakob Böhme (1575-1624): How is it possible to deduce the total reality from the concept of God without covering up any of the terrifying aspects of reality. I describe Böhme’s method as partly phenomenological (as an absorption into the material of experience, wrapped in the terminology of alchemy), partly theoretical (as a doctrine of the soul being the meeting-place of man and God). It is pointed out that when Böhme insists on the importance of experience, he does so in his capacity as theologian. The only way for God to enter into humanity is through the soul, and the only way for humanity to experience God is by making an effort to be mentally present. This is possible for humanity because its free will originates in the center of a mind (Gemüthe), which is at the same time an image of God. During this process human beings will experience both the good and the evil side of God. However, they will discover that evil transforms itself from being the contradiction of goodness to being its polar opposite. So far Böhme has, from the aspect of the psychology of religion, anticipated some central distinctions in the psychology of C.G. Jung (1875-1961).